THE DETERMINATION OF THE SHARPNESS DEPTH BORDERS AND CORRESPONDING PHOTOGRAPHY AND VIDEO RECORDING PARAMETERS FOR CONTEMPORARY VIDEO TECHNOLOGY - E. G. Zaytseva; A. A. Kisljuk (Приборы и методы измерений)
The method of determination of the sharpness depth borders was improved for contemporary video technology. The computer programme for determination of corresponding video recording parameters was created.